AusTraits, a curated plant trait database for the Australian flora - Daniel Falster (Nature Portfolio, 2021)
Measurement(s) plant trait Technology Type(s) digital curation Sample Characteristic - Organism Viridiplantae Sample Characteristic - Location Australia Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.14545755